2012
DOI: 10.5402/2012/898153
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Urocanic Acid Derivatives in Models Ex Vivo and In Vivo of Inflammatory Bowel Disease

Abstract: Urocanic acid (UCA) derivatives were tested for their anti-inflammatory activity in inflammatory bowel disease (IBD) in two models: ex vivo and an experimental mouse model. Ex vivo: inflamed colonic tissue was incubated in culture medium with or without the UCA derivatives. Biopsies, incubated with UCA derivatives, produced lower levels of proinflammatory cytokines IL-6 and IL-8 as compared to control biopsies. The same compounds also showed increased levels of IL-10, providing an additional indication for ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Urocanic acid is one metabolite which is involved histidine metabolism. The results of a recent study showed urocanic acid derivatives have anti-inflammatory effects on inflammatory bowel disease [34], supporting the decreased levels of urocanic acid in our AOSD patients. Indole, another important metabolite, is a product of amino acid (tryptophan) metabolism.…”
Section: Discussionsupporting
confidence: 81%
“…Urocanic acid is one metabolite which is involved histidine metabolism. The results of a recent study showed urocanic acid derivatives have anti-inflammatory effects on inflammatory bowel disease [34], supporting the decreased levels of urocanic acid in our AOSD patients. Indole, another important metabolite, is a product of amino acid (tryptophan) metabolism.…”
Section: Discussionsupporting
confidence: 81%
“…Like other branched SCFAs, valerate has been shown to modulate innate immune responses via specific receptors on macrophages and T cells [12,13]. In this and the previous study [3], we observed a higher content of urocanic acid (i.e., Bin number 7.86; uridine derivatives), which is known for its antiinflammatory activity [14]. Such immune-related metabolites, such as valerate and urocanic acid, are produced in the gut as a result of a local immune response that regulates host gut health.…”
Section: Discussionsupporting
confidence: 71%
“…Irradiation of the skin with ultraviolet B induces expression of the β‐endorphins which have analgesic and pigmentary effects . Synthesis of vitamin D (low in IBD, ) and urocanic acid which has been shown to suppress inflammation in models of IBD, also occurs in response to irradiation of the skin . Thus, selective manipulation of the skin by topically applied agents or UV‐irradiation, with its often underappreciated secretory and metabolic capacity, may offer new adjunctive therapies in GI diseases.…”
Section: Are There Other Possible Modes Of Interaction Between Gut Anmentioning
confidence: 99%